Tuned the refractive index and absorption edge for Fuchsin basic dye-doped (PVA-PVP-PEG) films: Linear and nonlinear optical characterization for blocking intense laser power - Mohammed, M. I.; Zahran, H. Y.; Ganesh, V.; Zyoud, Samer H.; Alabdulaal, T. H.; Aydin, Cihat; Yahia, I. S. (Elsevier, 2024)
The current investigation focused on creating dye -doped polymer blend films using a solution cast method with a composition of 60%PVA-30%PVP-10%PEG. These films displayed altered refractive index and absorption edge properties. Various characterization techniques, including XRD, FTIR, UV - vis spectroscopy, and optical limiting effects, were utilized to analyze the structural and optical features of the dyed films. The doped samples showed noticeable changes in the structural properties of the polymer matrix blend, as evident from their XRD and FTIR patterns. Incorporating FB dye into the blend resulted in absorption spectra appearing in multiple bands between 295 and 560 nm. For 532.8 nm He-Ne lasers, the FB/(PVA-PVP-PEG) blend was found to be ideal due to its transmittance CUT-OFF within the 200 - 600 nm wavelength range. The addition of FB dye had a significant impact on the optical characteristics of the polymer blend, leading to a shift in the absorption edge towards lower photon energy levels. The presence of FB dye was also observed to influence the refractive index ( n ) of the host polymer, indicating its potential for adjusting optical properties. Detailed investigations into the bandgap revealed a reduction in the bandgap of the host polymer due to the presence of the dye. Electronic transitions were further examined through the epsilon i ( omega ) parameter during the bandgap analysis, confirming the role of the dye in altering the optical bandgap. Overall, the synthesized FB/(PVA-PVP-PEG) polymeric films hold promise for various optoelectronic applications, including lasers, optical filters, communication devices, LEDs, and optical switches.
Keywords: Fuchsine basic dye; (PVA-PVP-PEG) blend matrix; XRD; Linear/nonlinear optics; Bandgap calculation; Laser CUT-OFF power attenuation